The influence of the thiotriazoline ointment with silver nanoparticles on morphological lesions of guinea pigs’ skin due to the local effects of ultraviolet rays at the remote terms after irradiation - Kitsyuk, N. I.; Zvyagintseva, T. V. (Journal of Education, Health and Sport, 2018)
Local ultraviolet irradiation of guinea pigs was performed and the morphofunctional state of the skin was investigated in terms of the delayed after irradiation under the conditions of using of the tiotriazolin ointment with SNP. It was established that under the influence of the ointment of thiotriazoline with SNP, a faster return to the norm of the structure of the skin and its morphometric parameters is noted: reduction of thickness and restoration of the normal structure of the epidermis in the period from the 15th to the 21st day, decrease of the index of density of fibroblasts to the value of norm by 28th day.